Study The Re-Use of Construction and Demolition Waste for Friendlier Environment: Waste Concrete and Waste Granite Aggregates - Mousa Hawraa Hasan; Kadhem Ali Abbas; Al-Bahrani Hussein Shakir; Jabal Qusay A.; Alasadi Laith (Civil and Environmental Engineering)
Waste aggregate concrete is the most common project in the world of construction. The waste materials are causing environmental pollution and hurting nature, the use of wastes give more clean nature and so that the use of wastes in concrete can solve these problems. This study aims to investigate the use of waste granite as coarse aggregate in concrete, studying also the use of waste concrete from old buildings as coarse aggregate, and then comparing between them. The study shows that waste black granite aggregate gives best results in compression and tensile strength, compressive strength increased from 33.6 to 43.9 MPa, Using waste concrete as coarse aggregate increased also compressive strength from 33.6 MPa for reference mix to 36.9 MPa with 100% replacement.